2013
DOI: 10.1371/journal.pone.0084161
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Increased Plasma ACTH Levels in Chronic Psychosocially Stressed Male Mice

Abstract: Mice exposed to chronic subordinate colony housing (CSC, 19 days), an established paradigm for chronic psychosocial stress, show unaffected basal morning plasma corticosterone (CORT) concentrations, despite enlarged adrenal glands and an increased CORT response to an acute heterotypic stressor. In the present study we investigate the mechanisms underlying these phenomena at the level of the pituitary. We show that both basal and acute stressor-induced (forced swim (FS), 6 min) plasma adrenocorticotropic hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 60 publications
4
23
0
1
Order By: Relevance
“…In line with what we found at the adrenal level, the increased capability of the CSC pituitary gland to produce and secret ACTH is mediated at least partly by corticotroph cell hyperplasia ( 155 ). Non-compromised functionality of those newly formed cells was suggested by comparable relative pituitary pro-opiomelanocortin protein expression between CSC and SHC mice ( 155 ).…”
Section: Chronic Subordinate Colony Housingsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with what we found at the adrenal level, the increased capability of the CSC pituitary gland to produce and secret ACTH is mediated at least partly by corticotroph cell hyperplasia ( 155 ). Non-compromised functionality of those newly formed cells was suggested by comparable relative pituitary pro-opiomelanocortin protein expression between CSC and SHC mice ( 155 ).…”
Section: Chronic Subordinate Colony Housingsupporting
confidence: 89%
“…In confirmation of this hypothesis, mice exposed to 19 days of CSC indeed show exaggerated plasma CORT concentrations, as well as an increased adrenal CORT content, when killed 5 min following termination of a mild acute heterotypic stressor (EPF) at the beginning of the light phase, despite the increase in plasma ACTH concentrations not differing from EPF-exposed SHC mice ( 142 ). Notably, when exposed to a more severe acute heterotypic stressor, i.e., 6-min of forced swimming, CSC mice even show an exaggerated ACTH response compared with SHC mice ( 155 ), likely to further enhance HPA axis reactivity toward a novel and severe enough heterotypic challenge in CSC mice. A facilitated ACTH response to a novel heterotypic challenge is thereby in line with other chronic stress studies [( 156 ); for review see ( 157 )].…”
Section: Chronic Subordinate Colony Housingmentioning
confidence: 99%
“…Pituitary adrenocorticotropic hormone (ACTH) is an important component of the hypothalamus-pituitary-adrenal (HPA) axis, which is essential for body homeostasis and survival during stress (Stevens and White, 2010;Fuchsl et al, 2013;Uchoa et al, 2014). It is influenced by various stimuli such as cortical release hormone (CRH), and to a lesser extent, by arginine vasopressin (AVP).…”
Section: Discussionmentioning
confidence: 99%
“…It is influenced by various stimuli such as cortical release hormone (CRH), and to a lesser extent, by arginine vasopressin (AVP). It receives a negative feedback suppression of cortisol from the adrenal glands (Fuchsl et al, 2013). A patch-clamp experiment for membrane potential in single rat corticotrophs showed that CRH triggered a sustained [Ca 2+ ]i elevation and membrane depolarization for corticotrophs (Lee and Tse, 1997), and ACTH secretion was related to an increase in the L-type Ca 2+ current (LeBeau et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…У мышей, подвергнутых хроническому психосоциальному стрессу (совместному проживанию доминантных и субординантных животных), повышались уровни АКТГ и кортикостерона в плазме крови, что сочеталось с неизменной экспрессией рецепторов КТРГ 1-го типа. Полагают, что в условиях хронического психосоциального стресса АВП является основным регулятором активности ГГНС [2,20]. В условиях хронического психологического стресса у человека также зафиксированы повышенные уровни АВП и кортизола в плазме крови и в цереброспинальной жидкости [5].…”
Section: роль аргинин-вазопрессина в модуляции ответа на стрессunclassified